Association of Smokeless Tobacco Use and Oral Cancer: A Systematic Global Review and Meta-Analysis. Issue 9 (22nd May 2018) - Asthana, Smita; Labani, Satyanarayana; Kailash, Uma; Sinha, Dhirendra N; Mehrotra, Ravi
Abstract: Introduction: Smokeless tobacco products have been linked to precancerous and cancers of oral cavity for long. Evidence was available on the association between smokeless tobacco (SLT) products and oral cancers at regional but not at global level. Present meta-analysis is aimed to evaluate the risk of oral cancer with the use of SLT products among "ever" versus "never" users. Method: Studies published for the period (1960–2016) are retrieved using Pubmed, Indmed, EMBASE, and Google Scholar search engines for the subject "ever" versus "never" users of SLT products and estimated the risk association with oral cancer. Summary odds ratios (relative risk) are estimated and meta-analysis was performed using random-effects model. Results: Thirty-seven studies from four of six WHO regions, Southeast Asia region (SEAR), the Eastern Mediterranean Region (EMR), Europe, and region of Americas (North and South) are included in the analysis. Significant risk with SLT products with oral cancer was found for SEAR (4.44, 95% CI = 3.51 to 5.61) and for EMR (1.28, 95% CI = 1.04 to 1.56). Significantly higher risk ( p < .001) was found for females (5.83, 95% CI = 2.93 to 11.58). Product wise analysis for different SLT products revealed various levels of risk viz. gutkha (8.67, 95% CI = 3.59 to 20.93), pan tobacco / betel liquid (7.18, 95% CI = 5.48 to 9.41), oral snuff (4.18, 50% CI = 2.37 to 7.38), Mainpuri tobacco (3.32, 95% CI = 1.32 to 8.36), and snus (0.86, 95% CI = 0.58 to 1.29). Conclusion: A significant positive association was observed between SLT use and the risk of oral cancer, in SEAR, EMRs, and among women users. Implications: The present meta-analysis demonstrates SLT product use and the risk of oral cancer at global level. Moreover, the present analysis provided data on the risk associated with individual SLT product. The results fulfil the gap in the data on independent effect of individual SLT product use on the outcome of oral cancer at global level, conclusively. Chewing SLT products was associated with higher risk of oral cancer than other types of SLT. This can serve as a useful tool for policy makers in forming strict policies in controlling SLT menace. Hence, we propose that in addition to smoking, efforts should be directed towards SLT product cessation as well in reducing oral cancer incidence.